EFEKTIVITAS PELAKSANAAN PROGRAM PEMBERDAYAAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL DALAM PENANGGULANGAN KEMISKINAN - Romi Saputra (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT This study discusses the effectiveness, supporting and inhibiting factors and formulate strategies to overcome obstacles in the implementation of the the Physically Empowerment Program Social Problems through the Joint Business Group in the Village Tanjunggading Bandarlampung City. The design used in this research using descriptive method with qualitative-inductive approach. Data analysis techniques used in descriptive research through data selection, data reduction and verification of data and using SWOT analysis in order to formulate strategies to overcome obstacles. The results of this study can be explained that the effectiveness of implementation of the People Empowerment Program Social Problems through the Joint Business Group (KUBE) in Tanjunggading Village generally been effective as seen from the achievement on Program Objectives, Increasing Income, and Ability to Solve Social Problems Increased Functionality of Members, but there are programs that can not be achieved in accordance with the objectives of the Sustainability Program, especially in the capital increase business. Supporting factors in the implementation of this program are active members in managing their business, Motivation members to implement and manage the business is high enough, the support from the community and coaching. While the inhibiting factors are: management and assistance that have not been effective, Human Resources (members) are still low, the absence of additional capital in order to develop joint business groups, marketing the products that have not reached the market and Unfair Business Competition. Appropriate strategies used to overcome barriers that permit service quality improvement (1) Human Resource Development (Member) KUBE and established a partnership with Micro Finance Institutions, (2) Change renewal Management KUBE and Utilizing advances in information technology, (3) Revitalization KUBE Organization, (4) Making Adjustments and evaluation of programs and activities are a priority and the provision of venture capital in order to increase business KUBE. Keywords: empowerment, social problems, poverty reduction